Event-Driven Conversational Workflow Architecture for Academic Service Automation Using n8n - Bonda Sisephaputra; Reisa Permatasari; Ronggo Alit; Azis Suroni; Rahmat Nugroho Saputra; Fathan Orvala; Dhava Gilang Ramadhan (International Journal of Computer, Network Security and Information System, 2026)
The digital transformation of higher education institutions has increased the demand for efficient academic service management systems. However, many existing digital academic service platforms primarily focus on providing online interfaces while the underlying administrative processes remain fragmented and manually coordinated. As a result, academic service requests such as document submissions and information inquiries often lack process transparency and structured workflow management. This study proposes an event-driven conversational workflow architecture for automating academic service processes. The proposed architecture integrates a conversational interface through WhatsApp messaging services, a workflow orchestration engine implemented using the n8n automation platform, and a cloud-based database using Supabase PostgreSQL. The system consists of three main workflows: knowledge base generation, information services using a Retrieval-Augmented Generation (RAG) approach, and document request services with multi-level approval processes. The research adopts the Design Science Research methodology to design and evaluate the proposed system architecture. A prototype system was implemented to demonstrate how academic service requests can be initiated through conversational interfaces and processed through event-driven workflow automation. The evaluation results show that the proposed architecture enables automated workflow orchestration, structured service state management, and improved service transparency.